Evaluation of energy efficient hybrid hollow plaster panel using phase change material/xGnP composites. (1st November 2017) - Wi, Seunghwan; Jeong, Su-Gwang; Chang, Seong Jin; Lee, Jongki; Kim, Sumin
Graphical abstract: Highlights: Hybrid panels were developed to storing the thermal energy effectively. The thermal conductivity of the PCM/xGnP composite was improved by 289%. The dynamic heat transfer analysis were performed to evaluate thermal performance. Up to 138.8 J/m 2 of energy was stored in the composite plaster panel. Abstract: Latent heat storage is considered to be the most effective way to use phase change material (PCM) to charge or discharge thermal energy as latent heat during the phase change period. In this study, hybrid hollow PCM/plaster composite panels were developed to prevent leakage during the solid-liquid phase change, and improve thermal performance using exfoliated graphite nanoplatelets (xGnP) and n -octadecane, which has high thermal conductivity and latent heat. The thermo-physical properties of xGnP and n -octadecane composites were analyzed by TCi thermal conductivity analyzer and differential scanning calorimetry (DSC). The thermographic analysis was performed for the thermal behavior of each prepared specimen during the heating and cooling process. In steady-state simulation analysis using HEAT2 software, the heat flow of the each specimen were analyzed as same boundary conditions for relative comparison. The thermal performance of the PCM/plaster composite panel using dynamic heat transfer analyzer showed reduced peak temperature and a time-lag effect. Furthermore, 138.8 J/m 2 latent heat was stored in the composite PCM, corresponding to approximately 51% of the available latent heat of the plaster panel.